Human Rights and Its Contested Legal Paradigm - Putro, Widodo Dwi (Journal of Southeast Asian Human Rights, 2023)
This article examines the philosophical foundation of the tension between two contested legal paradigms, namely the Sociological Jurisprudence and Historical School of Jurisprudence, and how the contestation affects human rights discourse in Indonesia. Sociological jurisprudence perceives law as a tool of social engineering, while the Historical School of Jurisprudence argues that the development of law is a subconscious and organic process. Such contested legal paradigms are relevant to the case of “kawin tangkap” or bride kidnapping in Sumba, East Nusa Tenggara Indonesia. This is certainly problematic from the human rights perspective, as it is contradictory to the protection of women and children. However, like in some other traditions, the practice has been continuously preserved in local communities. The article employs legal anthropology research methods to delve into the symbols and meanings embedded within the customary laws obeyed by local communities. Additionally, this research utilizes legal philosophy methodologies to scrutinize paradigmatic disputes among schools of thought and how these disputes affect the rights of women. The study also investigates variances in perspectives concerning customary law, state law, and human rights, particularly in the context of examining the tradition of captive bride kidnapping. The challenge lies in how human rights can be employed to foster a gradual shift away from deeply ingrained patriarchal cultural norms and practices, with the aim of enhancing the protection of women’s and children’s rights, all while preserving customary laws and the harmony of local communities. This article endeavors to address this challenge by advocating for effective communication strategies that encourage local communities to embrace human rights principles and abide by the law, driven by rational awareness. The findings from this research conscientiously raise awareness about human rights within local communities through effective legal communication, without disrupting the existing local order. Keywords: Human Rights, Historical School of Jurisprudence, Bride Kidnapping, Sociological Jurisprudence, Communication.